Apollo : the brilliant one - O'Connor, George (O'Connor, George. Olympians, 2016)
Apollo is the son of Zeus the King of Gods, born to his lover, a she-wolf named Leto. As Apollo reaches new highs and lows in pursuit of his destiny, his flaws threaten to destroy him and everything he touches. Features an Olympian family tree and resources for further information.